CHALLENGES IN LEARNING ENGLISH LANGUAGE AT INTERMEDIATE LEVEL - Niaz Hussain (International Journal of Contemporary Issues in Social Sciences, 2023)
This study investigates the challenges faced by intermediate-level students in learning English at intermediate level. The research identifies obstacles such as bilingual instructions, less-trained faculty, and a lack of systematic grammar teaching. Utilizing a quantitative approach, the study explores preferences, reluctance, and challenges through a questionnaire. Findings indicate a strong preference for reading, reluctance in listening, and challenges rooted in anxiety about making mistakes. The study underscores the need for targeted interventions to enhance English language education and improve learning outcomes at the intermediate level.